Social capital, psychological resilience and job burnout in hazardous work environments. (3rd April 2019) - Khaksar, Seyed Mohammad Sadegh; Maghsoudi, Tahereh; Young, Suzanne
ABSTRACT: The purpose of this study is to improve our understanding of the role of social capital in increasing psychological resilience and reducing job burnout. We collected data through a survey distributed among 234 employees in the National Iranian Gas Company as one of the top-10 international companies producing and refining natural gas derivatives. Seven hypotheses and a conceptual model were validated using structural equation modelling. We found social capital is crucial to reducing job burnout among employees who are exposed to hazardous work environments. We also found psychological resilience plays a facilitating role in promoting the negative correlation between social capital and job burnout. The findings assist to conceptualise relationships between managers and employees in hazardous work environments. This research provides empirical evidence that adopting the social capital perspective can assist organisations to improve the role of psychological resilience among employees, leading to reducing job burnout in the long-term.